The hardness of wheat and its relation to the moisture content - Stevens, Orin A. (My University, 1907)
Introduction: The terms “hard” and “soft” as commonly applied to wheats, are probably rather loosely used, with but a general and indefinite meaning. Certain red wheats are commonly referred to as hard, others as soft. On closer investigation it is foud, as does not seem at all unreasonable, that the degree of hardness varies in different varieties, in the same variety under different conditions, and in the grains of the same variety under any one condition. The common indication of hardness is found in the color of the grain. This varies in the red wheats from a clear reddish amber to an opaque red, yellow or whitish, the clear grain being “hard”, the others “soft”. By cutting the grains transversely with a knife the clear ones are found to hard and flinty, while the others are soft, white, and mealy. The grains of certain varieties may be characteristically of one type or the other, but in any given variety under ordinary conditions it is possible to select a perfect series of kernels showing all degrees from the entirely clear and flinty to the opaque and mealy. It may be and has been repeatedly shown that the flinty grains are considerably harder than the others. For instance in the following experiment the kernels of a certain sample which were entirely flinty or nearly so, were found to be 23.6 per cent harder than those which were not all, or only slightly flinty.
Citation: Stevens, Orin A. The hardness of wheat and its relation to the moisture content. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Wheat; Hardness of Wheat; Wheat Composition; Types of Grain in Wheat; Theses